Pengaruh Penggunaan Game Edukasi Baamboozle Terhadap Peningkatan Keterampilan Memahami Kosa Kata Bahasa Arab di Program Studi Bahasa dan Sastra Arab di UNUGIRI / The Impact of the Educational Game Bamboozle on Arabic Vocabulary Comprehension Skills Among Students in the Arabic Language and Literature Program Study at UNUGIRI - Miftahul Mufid; M Saeful Anwar (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
This study examines the impact of the educational game Bamboozle on Arabic vocabulary comprehension skills among students in the Arabic Language and Literature program at Sunan Giri Nahdlatul Ulama University (UNUGIRI). Using a pre-experimental one-group pretest-posttest design, the research involved 18 fourth-semester students. Data were collected through vocabulary tests, classroom observations, and student perception questionnaires. Results showed a significant improvement in vocabulary skills, with average scores increasing by 25.6% from pretest to posttest (Cohen's d = 1.99). Student participation rose from 70% in the first session to 95% in the final session. Additionally, over 90% of students reported positive perceptions of Bamboozle, citing increased motivation and easier vocabulary comprehension. These findings suggest that educational games like Bamboozle can effectively enhance Arabic vocabulary learning in higher education, offering an interactive and engaging alternative to conventional methods. This study contributes to the development of innovative Arabic language teaching strategies in the digital era.المستخلص: تبحث هذه الدراسة في تأثير لعبة بامبوزل التعليمية على تحسين مهارات فهم المفردات العربية لدى طلاب برنامج دراسة اللغة العربية وآدابها في جامعة الأمم المتحدة. إن استخدام التكنولوجيا في تعلم اللغة العربية مهم في العصر الرقمي لزيادة الدافعية وفعالية التعلم. وقد شملت الدراسة 18 طالبًا وطالبة من طلاب الفصل الدراسي الرابع، باستخدام تصميم ما قبل الاختبار التجريبي من مجموعة واحدة قبل الاختبار وبعده، وتم جمع البيانات من خلال اختبارات المفردات والملاحظات الصفية واستبيانات إدراك الطلاب. أظهرت النتائج تحسنًا ملحوظًا في مهارات المفردات، حيث ارتفع متوسط الدرجات بنسبة 25.6% من الاختبار القبلي إلى الاختبار البعدي (معامل كوهين د = 1.99). زادت مشاركة الطلاب من 70% في الجلسة الأولى إلى 95% في الجلسة الأخيرة. أبلغ أكثر من 90% من الطلاب عن تصورات إيجابية عن بامبوزل، مشيرين إلى زيادة الدافعية وسهولة فهم المفردات. تشير النتائج إلى أن الألعاب التعليمية مثل بامبوزل يمكن أن تعزز بشكل فعال تعلم المفردات العربية في التعليم العالي، وتقدم بديلاً تفاعليًا وجذابًا عن الأساليب التقليدية.